2022
DOI: 10.1007/s00216-022-04430-8
|View full text |Cite
|
Sign up to set email alerts
|

A new enzymatic assay to quantify inorganic pyrophosphate in plasma

Abstract: Inorganic pyrophosphate (PPi) is a crucial extracellular mineralization regulator. Low plasma PPi concentrations underlie the soft tissue calcification present in several rare hereditary mineralization disorders as well as in more common conditions like chronic kidney disease and diabetes. Even though deregulated plasma PPi homeostasis is known to be linked to multiple human diseases, there is currently no reliable assay for its quantification. We here describe a PPi assay that employs the enzyme ATP sulfuryla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Moreover, we performed an internal calibration and noted that the readout values could vary between different samples despite having been spiked with equal amounts of ATP, indicating that unknown factors in the plasma can affect the readout and may be responsible for part of the variation between different studies (Supplementary Table S1). The value of an internal ATP standard to obtain reliable measurement results was also recently shown by Lundkvist et al [30]. We cannot exclude that ethnic factors also affect PPi levels [31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Moreover, we performed an internal calibration and noted that the readout values could vary between different samples despite having been spiked with equal amounts of ATP, indicating that unknown factors in the plasma can affect the readout and may be responsible for part of the variation between different studies (Supplementary Table S1). The value of an internal ATP standard to obtain reliable measurement results was also recently shown by Lundkvist et al [30]. We cannot exclude that ethnic factors also affect PPi levels [31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 50%
“…As we used a citrate-based assay, such differences in reduction-both relative and absolute-indicate that the anticoagulant may significantly impact the PPi signal readout, as exemplified by the difference found between CTAD and EDTA by Sanchez-Tévar et al [15]. Such an effect of the anticoagulant was recently illustrated by Lundkvist et al, who showed that the amount of PPi detected depended on the anticoagulant used in the unfiltered plasma, with CTAD and heparin yielding higher concentrations compared to EDTA [30]. Moreover, we performed an internal calibration and noted that the readout values could vary between different samples despite having been spiked with equal amounts of ATP, indicating that unknown factors in the plasma can affect the readout and may be responsible for part of the variation between different studies (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 97%
“…A recent paper described the use of coupled enzymatic reactions using ATP sulfurylase to generate ATP and then quantified it by firefly luciferase activity (quantifying the bioluminescence) and included an internal ATP standard to correct for sample-specific interference since the authors aimed to determine the plasma levels of PPi ( Lundkvist et al, 2023 ). This assay shows excellent precision and accuracy, and interestingly, the anticoagulant EDTA blocked the conversion of ATP into PPi in plasma after blood collection.…”
Section: Ppases and Applicationsmentioning
confidence: 99%